Finite Element Analysis of A Strengthened Beam Deliberating Elastically Isotropic And Orthotropic Cfrp Material - Ghaedi, K.; Ibrahim, Z.; Javanmardi, A.; Jameel, M.; Hanif, U.; Rehman, S. K.; Gordan, M. (Journal of Civil Engineering, Science and Technology, 2018)
Using appropriate material properties for analyzing different models in academic and commercially available finite element software is one of the main concerns for design engineers and researchers. This paper demonstrates the importance of using appropriate material properties for the models to be considered by engineers during finite element modelling. Two reinforced concrete (RC) beams strengthened with Carbon Fiber Reinforced Polymer (CFRP) strips are investigated, considering the CFRP elements as elastically isotropic and orthotropic materials. To show the significance of the selective material properties, all properties of the models are chosen to be exactly the same for the two beams except for the CFRP strip. To validate the study, an RC beam is tested experimentally and the numerical results are compared to the experimental test. The results show that CFRP with isotropic or orthotropic properties has no significant influence on beam responses such as stresses, displacements and damage response under applied loadings.